Peranan personal inovative pada niat prilaku menggunakan waqf online dengan teori technology acceptance model - Qolbi, Ayun; Sukmana, Raditya; Tri Ratnasari, Ririn; Sekar Sari, Novi (Jurnal Ekonomika dan Bisnis Islam, 2024)
This research examines the relationship between personal innovativeness and the Technology acceptance model (TAM) on behavioral intention to use online waqf services. This study uses an online questionnaire, using 100 wakif who have used online waqf services in Indonesia. The data from questionnaires were analyzed using the structural equation model least square. Results showed personal innovativeness also influenced perceived ease of use and perceived usefulness. This study aims to offer insights into enhancing the usability and utility of online waqf services within Nazir institutions. The focus is on providing for the needs of wakifs, particularly those with limited familiarity or comfort with technology. this study represents the initial attempt to include personal innovation within a model for assessing the acceptance of online waqf services. In digital marketing, a particular focus exists on examining the variables influencing individuals' behavioral intentions to utilize online services.